Development of triple band planar inverted-H antenna for DCS, WIMAX and WLAN application - Ibrahim Jahun, Kabiru (2015)
In this research, a triple band inverted-H planar antenna for DCS1700, WiMAX2600 and WLAN3100 is presented. The antenna consists of square planar radiating patch with dual rectangular slots suspended above the FR4 dielectric substrate. The antenna is fed by using microstrip transmission line feeding, as it is easier to design. The antenna was designed and simulated using CST Microwave Studio. Different parameters such as shorting width, height of antenna, ground plane size and patch slot size that affect the antenna characteristics were also studied. The designed antenna was fabricated and assembled together and tested using network analyzer. The result obtained for the S11 parameter in measurement for the three bands are 1.764 GHz, 2.739 GHz and 3.17 GHz with return loss of -15.14 dB, -15.88 dB and -25.77 dB respectively. Comparison for the measurement and the simulation are carried out in terms of S11 parameter, bandwidth, VSWR, input impedance and radiation pattern.